'Take more time to actually listen': students' reflections on participation and negotiation in school. (15th January 2013) - McCluskey, Gillean; Brown, Jane; Munn, Pamela; Lloyd, Gwynedd; Hamilton, Lorna; Sharp, Stephen; Macleod, Gale
<x xml:space="preserve">Abstract</x> Behaviour in schools is an emotive topic and one of enduring political interest and sensitivity. The media often portrays schools as violent and dangerous places and young people as ever more unruly. This paper explores findings from a recent large‐scale national study on behaviour and focuses on the data from primary and secondary school students within this study. The comments and suggestions offered by students move beyond a discussion of behaviour to focus on the broader questions of participation, engagement and meanings of active citizenship in school.